Psychische Probleme in der Pandemie – Beobachtungen während der COVID-19-Krise - Fatke, Bastian; Hölzle, Patricia; Frank, Andreas; Förstl, Hans (DMW - Deutsche Medizinische Wochenschrift, 2020)
We have recently observed several clusters of psychiatric symptoms in the context of COVID-19: (1) increased anxiety in psychiatric in- and outpatients with different diagnoses; (2) more cases of domestic violence often associated with increased drug- or alcohol-consumption in offenders and victims; (3) a nihilistic “apocalyptic” syndrome of elderly patients cut-off from their families; (4) visual and acoustic hallucinoses due to pneumonia and sepsis-related confusional states. Cases of chloroquine-related toxicity have been reported elsewhere, but have not been observed in our hospital so far. Mental issues related to COVID-19 reported from China and practical recommendations are briefly summarized. Many patients with serious mental disorders will suffer world-wide due to a reallocation of medical, social and financial ressources.
Keywords: Apokalypse-Syndrom; Chloroquin; Halluzinose; häusliche Gewalt; Verwirrtheitszustand